1992
DOI: 10.1002/gcc.2870040105
|View full text |Cite
|
Sign up to set email alerts
|

A complex genetic rearrangement in a t(10;14)(q24;q11) associated with T‐cell acute lymphoblastic leukemia

Abstract: The t(10;14)(q24;q11) is observed in the leukemia cells of 5-10% of cases of T-cell acute lymphoblastic leukemia (T-ALL). Recently, molecular analyses of a number of these translocations revealed simple reciprocal translocations between the T-cell receptor delta chain gene (TCRD) and a region of 10q24. We have characterized, at the molecular level, a t(10;14)(q24;q11) in a patient with T-ALL. The translocation in this case, in contrast to the previous cases, is part of a complex genetic rearrangement. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Losses in 10q and 17p were also found in the recent study of Mao et al (2002). Aberrations of the chromosome 10q region have, in addition to CTCL (Berger and Bernheim, 1987;Schlegelberger et al, 1994;Thangavelu et al, 1997), been reported for other hematological malignancies, including acute T cell leukemias (Park et al, 1992), B cell lymphomas (Siebert et al, 1998), and other non-Hodgkin lymphomas (Speaks et al, 1992). This region encodes tumor suppressor genes such as PTEN (10q23.3), MXI1 (10q25-26), and DMBT1 (10q25-26).…”
Section: Discussionmentioning
confidence: 64%
“…Losses in 10q and 17p were also found in the recent study of Mao et al (2002). Aberrations of the chromosome 10q region have, in addition to CTCL (Berger and Bernheim, 1987;Schlegelberger et al, 1994;Thangavelu et al, 1997), been reported for other hematological malignancies, including acute T cell leukemias (Park et al, 1992), B cell lymphomas (Siebert et al, 1998), and other non-Hodgkin lymphomas (Speaks et al, 1992). This region encodes tumor suppressor genes such as PTEN (10q23.3), MXI1 (10q25-26), and DMBT1 (10q25-26).…”
Section: Discussionmentioning
confidence: 64%
“…The t(10;14)(q24;q11) translocation occurs in about 10% of T-cell acute lymphoblastic leukemias. This involves a reciprocal translocation between chromosomes 10 and 14, wherein breakage on chromosome 10 occurs at the HOX11 (TCL3) gene, which encodes a transcription factor (3)(4)(5)(6). Breaks at HOX11 occur at the 5= end of the gene, due to an unknown mechanism, resulting in its juxtaposition to the T-cell receptor (TCR) locus.…”
mentioning
confidence: 99%
“…Earlier investigators had proposed a V(D)J recombinationmediated mechanism for HOX11 breakage, due to the presence of cryptic RSS near the patient breakpoints (3)(4)(5)(6). However, the cryptic sequence at the breakpoint region was shown not to be recognized by the recombination-activating gene (RAG) complex (11).…”
mentioning
confidence: 99%
“…11 Cytogenetic analyses have shown that 4% of T-ALL cases contain a t(10;14)(q24q11) translocation, where the HOX11 gene is juxtaposed to the D␦2, D␦3 or J␦1 gene segments of the TCR␦ at locus 14q11. 5,[12][13][14][15][16] In addition, a variant translocation t(7;10)(q35;q24) is associated with 1% of T-ALL, such that the HOX11 gene is juxtaposed to the TCR␤ gene at locus 7q35. 16,17 Sequence analysis of 15 out of 19 reported t(10;14)(q24;q11) translocations demonstrated that the breakpoints on the 10q24 locus were clustered within a 1 kb region directly upstream of the HOX11 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies of some t(10;14)(q24;q11) and t(7;10)(q35;q24) breakpoints have shown that heptamer and/or nonamer-like sequences which normally signal V(D)J recombination were present in the DNA flanking the 10q24 breakpoints. 1,5,[13][14][15]17,18 The net result of errors in the normal rearrangement process was the expression of a 2.3 kb transcript, when the HOX11 gene was juxtaposed to the TCR locus.…”
Section: Introductionmentioning
confidence: 99%